Internet-based supply chain management analysis - Uttapol Smutkupt (2018)
Today Supply Chain Management is one of valuable techniques for most organizations. Supply Chain Management can help organizations to improve operations including lower inventories, lower costs, higher productivity, greater agility, shorter lead times, higher profits and greater customer loyalty. As a result, many organizations try to implement Supply Chain Management with their partners. Not only the Supply Chain Management, but also the performance of the Supply Chain Management is very important. If these organizations need to implement the concept, they also need to measure the result. Also, the mathematical model that uses to evaluate the Supply Chain Management of Northern Thai SMEs is developed. This model evaluates working methods and the performance of organizations from the viewpoint of Supply Chain Management. However, if this model is stand-alone software, the benefit is limited. Information technology is applied to create the model on-line, so many organizations can get more benefit. PHP language and MySQL database are used to develop a web-base application to measure how well the Supply Chain Management implementation. This application allows new users to register in the database. If users who already registered in the database login to the application, users will be asked to answer 62 questions in 6 sections of Supply Chain Management. All 6 sections are Customer Information, Finance Information, Internal Process Data, Learning and Growth Data, Internal Supply Chain Data, and Integrated Supply Chain Management. After users answer all questions, all answers are saved in the database. Then, the scores will be calculated and compared to the best score of the same type of organization. This is a benchmarking application showing the performance of each organization and the best same type organization. The organization score (between 0-1) is calculated by using desirability function. Moreover, not only the score of an organization can be calculated but the score of a supply chain can also calculate. The supply chain score is calculated by integrating the score of each organization in the supply chain together. The supply chain score shows how each organization that link together in the supply chain work. The high score means they can work very well with each others whereas the low score mean they need to be improved. This is a supply chain analysis application showing the performance of its supply chain. Based on a benchmarking application and a supply chain analysis application, all results are reported in numbers, percentages and graphs.